Hubungan Frekuensi Hospitalisasi Dengan Tingkat Kecemasan Anak Usia Sekolah Di RSUP Dr. Soeradji Tirtonegoro Klaten - Siwahyudati, Siwahyudati; , Endang Zulaicha S., S.Kp, M.Kep (2017)
Background: Hospitalitation is state that requires children to be hospitalized because of certain circumtances. The impact of hospitalitation will cause psychological reaction in children in the form of anxienty. Anxienty will cause children to be uncooperative and uncommunicate that influent the long of children hospitalitation and cure. By 2015, there is a child patient 1,797 admitted to was Dr. Suradjji Tirtonegoro amounted to 32% of the amount of the patient's school age children. The frequency of hospitalitation on patient hospitalized more than once can decrease chlid's anxiety and increase the use of hospitalitaion. Research Objectives: knowing the relationship of hospitalitation frequency with a level of anxiety in school age children was Dr. Suradji Tirtonegoro Klaten. Research Methodes: the research was included in kind of observational correlative quantitative research, with the approach of crossectional design. Engineering samples are accidental sampling with technical with total sampling as much as 42 respondents. Technical analyisis of the test data using the Spearman Rank Test. Result of research: Charasteristic of respondent based on the gender of the majority was male as much as 23 (54,8%). Hospitalitation frequency as much as 21 ( 50%) respondents in patiens which first hospitalized and 21 (50%) and 21 (50%) in patient which more than once hospitalized. Most was average anxienty as much as 26 ( 61,9%). The result of research using The Spearman Rank Test obtained p value= 0.000 and rho 0.556. Summary: there is relationship beetwen frequency of hospitalitation significantly with the level of anxienty in children of school age.